Distancing, self‐esteem, and subjective well‐being in head and neck cancer. Issue 11 (28th January 2015) - Devins, Gerald M.; Wong, Janice C.; Payne, Ada Y. M.; Lebel, Sophie; Lee, Ruth N. F.; Mah, Kenneth; Irish, Jonathan; Rodin, Gary
Abstract: Background: Distancing (i.e. construing oneself as dissimilar to a negatively‐stereotyped group) preserves self‐esteem and may benefit other domains of subjective well‐being. Head and neck cancer (HNC) is stigmatized because major risk factors include avoidable lifestyle variables (smoking, alcohol consumption, and human papilloma virus). Because the benefits of coping efforts, such as distancing, are most evident when people are under stress, we hypothesize that the psychosocial benefits of distancing will be most pronounced when cancer and its treatment interfere substantially with participation in valued activities and interests (i.e. high illness intrusiveness). Objective: To test whether distancing preserves self‐esteem and other domains of subjective well‐being (SWB) in HNC, especially when illness intrusiveness is high. Methods: Five hundred and twenty‐two HNC outpatients completed a semantic‐differential measure of perceived similarity to the 'cancer patient' and measures of illness intrusiveness, self‐esteem, depressive symptoms, and psychological well‐being in structured interviews. Evaluations of the 'cancer patient' reflected cancer stereotypes. Results: A statistically significant interaction supported the central hypothesis: When people held negative stereotypes, those who construed themselves as similar to the 'cancer patient' reported lower self‐esteem than those who construed themselves as dissimilar. Distancing did not benefit other SWB variables. Some results were counter‐intuitive: e.g. Emotional distress increased with increasing illness intrusiveness when people did not hold negative cancer stereotypes, but when they held highly negative stereotypes, distress decreased with increasing illness intrusiveness. Conclusions: Overall, distancing preserved self‐esteem in people with HNC and was associated with benefits in other SWB domains. Copyright © 2015 John Wiley & Sons, Ltd.